Digesting the data - Effects of predator ingestion on the oxygen isotopic signature of micro-mammal teeth. (15th November 2017) - Barham, Milo; Blyth, Alison J.; Wallwork, Melinda D.; Joachimski, Michael M.; Martin, Laure; Evans, Noreen J.; Laming, Belinda; McDonald, Bradley J.
Abstract: Biogenic minerals such as dental apatite have become commonly analysed archives preserving geochemical indicators of past environmental conditions and palaeoecologies. However, post-mortem, biogenic minerals are modified due to the alteration/replacement of labile components, and recent moves to utilise micro-mammal tooth δ 18 O signatures for refined Cenozoic terrestrial palaeoclimate reconstructions has lacked consideration of the chemical effects of predator digestion. Here, the physical and chemical condition of laboratory-raised mouse ( Mus musculus ) teeth have been investigated in conjunction with their bulk phosphate and tissue-specific δ 18 O values prior, and subsequent, to ingestion and excretion by various predator species (owls, mammals and a reptile). Substantial variability (up to 2‰) in the δ 18 O values of both undigested teeth and those ingested by specific predators suggests significant natural heterogeneity of individual prey δ 18 O. Statistically distinct, lower δ 18 O values (∼0.7‰) are apparent in teeth ingested by barn owls compared to undigested controls as a result of the chemically and enzymatically active digestive and waste-pellet environments. Overall, dentine tissues preserve lower δ 18 O values than enamel, while the greatest modification of oxygen isotope signals is exhibited in the basal enamel of ingested teeth as a result of its incompletely mineralised state. However, recognition of 18 O-depletion in chemically purified phosphate analyses demonstrates that modification of original δ 18 O values is not restricted to labile oxygen-bearing carbonate and organic phases. The style and magnitude of digestive-alteration varies with predator species and no correlation was identified between specific physical or minor/trace-element (patterns or concentrations) modification of ingested teeth and disruption of their primary oxygen isotope values. Therefore, there is a current lack of any screening tool for oxygen isotope disruption as a result of predation. These results point to the need for careful application of the micro-mammal oxygen isotope palaeoenvironmental proxy in future studies. Highlights: Heterogeneity (∼2‰) of mouse PO4 requires multiple samples for accurate δ 18 O means. Mature enamel 1° target for O-isotope data, basal enamel incompletely mineralised. Statistically significant 18 O-depletion (∼0.7‰) in barn owl-ingested rodent teeth. Variable physical and trace-element modification of teeth during digestion by predators. Digestion-modification of δ 18 O not restricted to labile phases and includes PO4 .